Murine PAIP1 stimulates translation of spermiogenic mRNAs stored by YBX2 via its interaction with YBX2. Issue 2 (5th October 2018) - He, Yue; Lin, Yu; Zhu, Yu; Ping, Ping; Wang, Guishuan; Sun, Fei
Abstract: The expression of many genes during the postmeiotic stages of spermatogenesis is largely regulated by germ cell-specific RNA-binding proteins at the level of posttranscription. One of these RNA-binding proteins, YBX2, participates in mRNA storage and regulation of translation in haploid spermatids. How YBX2-stored mRNAs become translationally competent during spermiogenesis remains unknown. In the present study, we report for the first time that YBX2 interacts with PAIP1, a protein translation enhancer, in vitro and in vivo. In murine testes, PAIP1 is highly expressed and colocalizes with YBX2 in round spermatids. Using sequential RNA immunoprecipitation and sequence analysis, we identified a group of spermiogenic mRNAs indirectly bound by PAIP1 through YBX2. Translation of mRNAs bearing the YBX2 target sequence was significantly blocked by YBX2 protein, but was reinitiated when YBX2 was coexpressed with PAIP1 in vitro. Taken together, these results indicate that PAIP1 regulates the translation of YBX2-masked mRNAs during spermiogenesis, and we propose this YBX2–PAIP1 interaction plays an important role in male germ cell development. Abstract : PAIP1 interacts with YBX2 in the testis and stimulates translation of spermiogenic mRNAs stored by YBX2.